Efficacy of religious integrated counselling in fostering hospitality and religious harmony in Nigeria: counsellors’ perspective - Afolasade Airat Sulaiman (Konselor, 2020)
This study surveyed counsellor’s opinion on the efficacy of religious integrated counselling in fostering hospitality and religious harmony in Nigeria. The sample for the study was 120, Counselling for Hospitality and Religious Harmony Questionnaire (CHRHQ) was used for data collection Content Validity Index of CHRHQ was 0.85 and 0.87 reliability. Majority agreed that integrated religious counselling could foster hospitality and encourage religious harmony through competent and appropriate use of different skills and techniques. Also, majority had integrated religion into counselling. No sex difference was found on counsellors’ perception of ways to foster hospitality and religious harmony through counselling, but sex difference exists in the integration of religion into counselling. It was therefore recommended that learning about different religions should become part of counsellors’ training; every mainstream counsellor must take a course in the two major religions – Christianity and Islam, and massive enlightenment programmes through the media are required.